DNA damage checkpoints in stem cells, ageing and cancer - Sperka, Tobias; Wang, Jianwei; Rudolph, K. Lenhard (Nature reviews. Molecular cell biology, 2012)
Key Points Checkpoint responses have diverse roles in adult stem cells depending on the genetic context and the level of DNA damage in tissues and stem cells, which increases with age. Thus, the role of checkpoints in stem cells may change during ageing. The activation of checkpoint genes in response to DNA damage accumulation leads to depletion of stem cells by induction of apoptosis or differentiation. Whether checkpoints induce stem cell senescence remains unclear. DNA damage checkpoint genes influence the maintenance and functionality of undamaged stem cells in adult tissues by controlling self-renewal, quiescence and differentiation. The functions of checkpoint genes in undamaged stem cells seem to be independent of and sometimes contrasting to their roles in DNA damage responses. The deletion of checkpoint genes can lead to defects in quiescence and premature exhaustion of stem cells or to enhanced self-renewal and transformation of stem cells. The deletion of checkpoint responses improves stem cell maintenance in the context of high levels of DNA damage. This can also result in improved tissue maintenance, when chromosomal stability is maintained at the stem cell level. In addition, checkpoint deletion can impair tumour initiation and maintenance by fuelling damage accumulation in cancer stem cells. An increase in the gene dosage of naturally regulated checkpoint genes can lead to improved clearance of molecular damages, prolonged tissue maintenance and decreased carcinogenesis in the context of low levels of DNA damage. Whether these effects are stem cell-dependent is not known. Like all cell types, stem cells are subject to DNA damage, which results in the activation of checkpoint proteins, for example p53. These checkpoint responses lead to the clearance of damaged cells by cell-intrinsic and cell-extrinsic mechanisms, preventing carcinogenesis, but may also impair stem cell and tissue maintenance, thereby promoting ageing. DNA damage induces cell-intrinsic checkpoints, including p53 and retinoblastoma (RB), as well as upstream regulators (exonuclease 1 (EXO1), ataxia telangiectasia mutated (ATM), ATR, p16 INK4a and p19 ARF ) and downstream targets (p21, PUMA (p53 upregulated modulator of apoptosis) and sestrins). Clearance of damaged cells by cell-intrinsic checkpoints suppresses carcinogenesis but as a downside may impair stem cell and tissue maintenance during ageing. Modulating the activity of DNA damage checkpoints can either accelerate or decelerate tissue ageing and age-related carcinogenesis. The outcome depends on cell-intrinsic and cell-extrinsic mechanisms that regulate the clearance of damaged cells and on the molecular context in ageing tissues, including the level of DNA damage accumulation itself.